PENGARUH PENGUMUMAN KEBIJAKAN 7 DAY REPO RATE DI BURSA EFEK INDONESIA 2016 ( STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - admin, Adi Saputro B1021131085 (Jurnal Manajemen Update, 2017)
ABSTRACT               This study was conducted to determine the effect of the announcement of new interest rate policy 7 Day Repo Rate that against abnormal return and trading volume activity on banking shares listed on the Indonesia Stock Exchange period April 2016. This research is a type of research Event Study that studies the market reaction to an event Whose information is published as an announcement. The period of this study is 4 days before, 1 day at the event, and 4 days after the announcement of the 7 Day Repo Rate policy.               Data collection techniques of this study include documentation and data. The population in this study is the banking sector listed on the Indonesia Stock Exchange as of April 2016. The study with Abnormal Return and Trading Volume Activity variables was tested by using kolmogorov-smirnov normality test and wilcoxson different test.               The result of this research is statistically there is no significant difference of Abnormal Return and Trading Volume Activity. In other words, the change of interest rate policy from the Bank Indonesia Interest Rate (SBI) to 7 Day Repo Rate does not contain any meaningful information for investors so that the reaction caused by the market is not  significant. Kata Kunci : Interest Policy Rate,7 Day Repo Rate,Indonesia Stock             Exchange,Trading Volume Activity,Abnormal Return